Comparison between grass-silages of different dry matter content fed to reindeer during winter - Nilsson, Anna; Olsson, Ingemar; Lingvall, Per (Rangifer, 1996)
A study was made of whether the dry matter content of silage influenced performance when 17-month-old male reindeer were fed solely silage outdoor during winter. Two kinds of round-baled silages with different wilting times were offered to the animals; low dry matter (LDM silage) with a mean of 39% DM, or high dry matter (HDM silage) with a mean of 53% DM. The 115 reindeer were allotted to slaughter at the start of the experiment in October or to be fed until slaughter in January or March. During the first three weeks of the experiment small amounts of lichens were mixed with the silages and the reindeer adapted to the feeding without problems. The daily intake of DM did not differ significantly between reindeer fed the LDM or the HDM silage despite a highly significant difference in daily silage intake. This resulted in small but significantly higher gains in live weight for animals fed the LDM silage, caused by increased weight of the rumen content. All groups of reindeer either retained or lost carcass weight during the experiment, and no improvements or differences were obtained between the kinds of silages in carcass assessment or gains in fat in the abdominal cavity. Animals slaughtered in January had a lower carcass weight and dressing percentage than reindeer slaughtered in October and March. Environmental conditions during the experiment were good but nonetheless mobbing and illness still occurred. The present results concur with those of earlier studies suggesting that it seems to be the bulk of the ration rather than the dry matter content of the silage that limits the intake.